Optimizing the Dialogic Patrol of the Sabhara Patrol Unit in the Prevention of Motor Vehicle Theft in the Pekanbaru Police Area During the Covid-19 Pandemic - Septian Alfayyet (Police Studies Review, 2021)
The Covid-19 pandemic that has attacked all regions in Indonesia has caused a decline, especially in the economic sector. This has led to an increase in several crimes in society, in this case the crime of motor vehicle theft in Pekanbaru. The purpose of this research is to explain the implementation of the Sabhara Dialogic Patrol in preventing the crime of theft. It also aims to explain the factors that influence the implementation of the Sabhara unit's dialogical patrol. The methodology used is a qualitative approach. Sources of data used in this study are primary and secondary data sources. The research method used is descriptive analysis research which aims to get a real picture of what happened at the Pekanbaru Police by using data collection techniques in the form of interviews, observation and document review. This research was conducted in the jurisdiction of the Pekanbaru Police which focuses on patrol activities carried out by the Sabhara unit in preventing motor vehicle crimes. This study uses the conceptual theory of crime prevention, Management Theory (P.O.A.C), and uses the theory of SWOT analysis. This study also uses the Dailogical Patrol concept, the Sabhara concept and the motor vehicle theft concept. These three concepts are combined concepts used in this study to support the relationship between the background problems used. The results of the study explain that the implementation of the Patrolidialogic Unit of the Sabhara Polresta Pekanbaru has referred to the Perkbaharkam Polri No. 1 year 2017, but there are some things that are not right. There are two factors that influence this, namely the strength factor, namely the existence of a patrol box program which is a means of leadership control, then there is a weakness factor in the lack of qualified personnel and personnel, lack of infrastructure.